PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA CANVA PADA PEMBELAJARAN IPAS KELAS IV SDN 26 RIMBO KALUANG KOTA PADANG - idzil andesti; Hamimmah (STKIP Subang, 2025)
This study was motivated by the low learning outcomes of students in IPAS (Science and Social Science) learning. The purpose of this study is to describe the implementation of the Problem Based Learning model assisted by Canva media to improve student learning outcomes in IPAS for Grade IV students at SDN 26 Rimbo Kaluang, Padang City.This research is a classroom action research using both qualitative and quantitative approaches, conducted in four stages: planning, implementation, observation, and reflection. It was carried out in two cycles: the first cycle consisted of two meetings, and the second cycle consisted of one meeting. The research data were collected through lesson plan evaluations, learning implementation observations, and student learning outcomes using document analysis, tests, and non-test techniques. The subjects of this study were the teacher and 24 fourth-grade students, consisting of 12 male and 12 female students.The results showed that the Lesson Plan Evaluation activity in Cycle I reached an average percentage of 85.41% with a Good (B) qualification and increased in Cycle II to 91.66% with a Very Good (A) qualification. In the learning implementation observation, teacher activity in Cycle I scored an average of 87.49% (Good) and increased to 92.85% (Very Good) in Cycle II. Student activity also increased from 87.49% (Good) in Cycle I to 92.85% (Very Good) in Cycle II. Student learning outcome scores increased from an average of 72.38 (Fair) in Cycle I to 92.71 (Very Good) in Cycle II. Attitude assessments based on students' dominant attitudes showed that in Cycle I, 9 students demonstrated positive attitudes and 7 showed negative attitudes. In Cycle II, 13 students demonstrated positive attitudes while only 3 exhibited negative attitudes. Based on these findings, it can be concluded that the Problem Based Learning model assisted by Canva media can effectively improve student learning outcomes in IPAS.